Sculling and unroll-body-action techniques in the thrust movement of synchronised swimming based on three-dimensional motion analysis - Homma, Mi.; Nakagawa, K.; Ito, K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The thrust movements both under and above water of nine top-level synchronised swimmers were analysed using 3D DL T method. Peak height, height of shoulder, elbow and wrist, unroll time, sculling time, maximum vertical velocity of the body's centre of gravity, wrist velocity, hip and shoulder angle are analysed as kinematic parameters. Since the peak height index (peak height/body height) and the maximum vertical velocity of the body's centre of gravity were related significantly, it is necessary to increase the vertical velocity of the body's centre of gravity in order to increase the peak height. Swimmers with a high peak height index demonstrated a shorter unroll time with a quick extension of the hips. Furthermore, in sculling, the arm's position was maintained near the surface of the water during the arms pull phase. The arm's position was closer to the water surface with a higher vertical velocity of the wrists during the arms turn. lt was found that important techniques to improve peak height in thrust movement, are to unroll with a shorter time, and to not lower the arms at the beginning of thrust movement and to turn arms rapidly and catch the water closer to the surface with horizontal forearms.